2016
DOI: 10.1099/jmm.0.000226
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Candida albicans biofilm formation and modulation of gene expression by probiotic cells and supernatant

Abstract: Oral candidiasis is a disease caused by opportunistic species of Candida that normally reside on human mucosal surfaces. The transition of Candida from budding yeast to filamentous hyphae allows for covalent attachment to oral epithelial cells, followed by biofilm formation, invasion and tissue damage. In this study, combinations of Lactobacillus plantarum SD5870, Lactobacillus helveticus CBS N116411 and Streptococcus salivarius DSM 14685 were assessed for their ability to inhibit the formation of and disrupt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 51 publications
9
47
0
Order By: Relevance
“…The HWP1 gene is known to encode a major C. albicans protein that is involved in several functions, including cell wall assembly, intracellular signalling and hyphal development (Sundstrom et al 2002;Biswas et al 2007;Chaffin 2008). In our expression profiles, CPH1, ALS3 and HWP1 were downregulated in the presence of cells primarily when the biofilms were treated with the L. rhamnosus supernatant, which was in agreement with the results of other studies (K€ ohler et al 2012;Bandara et al 2013a,b;James et al 2016). We speculated that the modulation of hypha-specific gene expression in C. albicans induced by Lactobacillus was one likely reason for the decrease in Candida filamentation (Bandara et al 2013a,b).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The HWP1 gene is known to encode a major C. albicans protein that is involved in several functions, including cell wall assembly, intracellular signalling and hyphal development (Sundstrom et al 2002;Biswas et al 2007;Chaffin 2008). In our expression profiles, CPH1, ALS3 and HWP1 were downregulated in the presence of cells primarily when the biofilms were treated with the L. rhamnosus supernatant, which was in agreement with the results of other studies (K€ ohler et al 2012;Bandara et al 2013a,b;James et al 2016). We speculated that the modulation of hypha-specific gene expression in C. albicans induced by Lactobacillus was one likely reason for the decrease in Candida filamentation (Bandara et al 2013a,b).…”
Section: Discussionsupporting
confidence: 92%
“…,b; James et al . ). We speculated that the modulation of hypha‐specific gene expression in C. albicans induced by Lactobacillus was one likely reason for the decrease in Candida filamentation (Bandara et al .…”
Section: Discussionmentioning
confidence: 97%
“…To determine the effects of CFS in RPMI 1640 + 10% FBS broth on the transcription of C. albicans genes related to yeast-to-hyphae transition, gene expression levels of GSP1 , NRG1 , TEC1 , EFG1 , EAP1 , SAP5, ALS3 , HWP1 , and ECE1 were evaluated by two-step qRT-PCR (Sun et al, 2015; James et al, 2016). Total RNA of C. albicans was extracted using a Yeast RiboPure RNA Purification kit (CoWin Biosciences, Beijing, China).…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that these probiotics are effective in inhibiting the biofilm formation and also removing of the preformed biofilms of C. albicans. 43 Therefore, it is rational to claim that probiotics and their derivatives can be used as both prophylactic and treatment biodrugs.…”
Section: Probiotics Influence Gene Expression Of Pathogenic Biofilmsmentioning
confidence: 99%